Phenotyping COPD Patients with Emphysema Distribution Using Quantitative CT Measurement; More Severe Airway Involvement in Lower Dominant Emphysema - Park J; Kim EK; Lee SH; Kim MA; Kim JH; Lee SM; Lee JS; Oh YM; Lee SD; Lee JH (International Journal of COPD, 2022)
Jisoo Park,1 Eun-Kyung Kim,1 Se Hee Lee,1 Mi-Ae Kim,1 Jung-Hyun Kim,1 Sang Min Lee,2,3 Jae Seung Lee,4,5 Yeon-Mok Oh,4,5 Sang-Do Lee,4,5 Ji-Hyun Lee1 On behalf of the KOLD Study Group1Department of Pulmonology, Allergy and Critical Care Medicine, CHA Bundang Medical Center, CHA University, Seongnam-si, Gyeonggi-do, Republic of Korea; 2Department of Radiology, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea; 3Research Institute of Radiology, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea; 4Department of Pulmonary and Critical Care Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea; 5Clinical Research Center for Chronic Obstructive Airway Diseases, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of KoreaCorrespondence: Ji-Hyun Lee, Department of Pulmonology, Allergy and Critical Care Medicine, CHA Bundang Medical Center, CHA University, 59, Yatap-ro, Bundang-gu, Seongnam-si, Gyeonggi-do, 13496, Republic of Korea, Tel +82-31-780-5205, Fax +82-31-780-2992, Email plmjhlee@cha.ac.krPurpose: We explored the differences in clinical manifestations of COPD patients regarding emphysema distribution along with evidence of airway involvement in chest computed tomography (CT) scans.Patients and Methods: The patients were divided into three groups according to the emphysema distribution: the upper dominant (UD), lower dominant (LD), and homogeneous (HD) groups. Airway wall thickness was quantitatively measured and the presence of bronchiectasis and/or bronchial wall thickening (BE/BWT) was visually assessed. Baseline characteristics including the evidence of airway involvement and long-term outcomes were compared among the three groups. Non-severe patients of each group were first treated with 3 months of ICS/LABA combination after 2 weeks of wash-out period and lung functions before and after the treatment were compared.Results: Of the 425 patients, 141 were in the UD, 107 in LD, and 177 in HD. The LD had more severe airway obstruction with lower emphysema index (EI) than the UD (LD vs UD; FEV1, 49.5– 14.9 vs 54.6– 16.5; EI, 21.0 [IQR: 14.0– 33.1] vs 26.3 [IQR: 15.8– 39.0]). The LD showed thicker airways (higher WA% and Pi10) and more severe air trapping (higher RV and RV/TLC) than UD. A larger proportion of patients in LD had BE/BWT (35.5% in LD vs 11.3% in UD). In LD, more patients experienced acute exacerbations and the time to first exacerbation was shorter than UD. Non-severe patients in LD treated with 3 months of ICS/LABA combined inhalers showed a notable reduction of RV than UD (LD vs UD; − 531.1– 936.5 vs − 86.5– 623.5).Conclusion: The LD showed a more prominent airway involvement than UD, which may cause more frequent exacerbations and a marked reduction of RV after the ICS/LABA combination treatment in LD. Phenotyping of the COPD patients using quantitatively measured emphysema distribution would be useful for predicting treatment response and exacerbation.Keywords: pulmonary disease, chronic obstructive, computed tomography, emphysema